- 鐵幣
- 9 元
- 文章
- 8 篇
- 聲望
- 23 枚
- 上次登入
- 07-5-10
- 精華
- 0
- 註冊時間
- 07-4-22
- UID
- 378758
|
令f(x)=(x-a)(x-b)(x-c)
則f(x)=x^3-(a+b+c)x^2+(ab+bc+ca)x-abc
(1)
如果|y|<1,則-1<y<1
可推得y+1>0,1-y>0
(2)
因為|a|<1,|b|<1,|c|<1
所以有:
(a+1)>0,(b+1)>0,(c+1)>0
(1-a)>0,(1-b)>0,(1-c)>0
(3)
由(2)知:
(1-a)(1-b)(1-c)>0
f(1)=(1-a)(1-b)(1-c)>0
1-(a+b+c)+(ab+bc+ca)-abc>0
(4)
由(2)知:
(1+a)(1+b)(1+c)>0
f(-1)=(-1-a)(-1-b)(-1-c)=-(1+a)(1+b)(1+c)
-f(-1)=(1+a)(1+b)(1+c)>0
-[-1-(a+b+c)-(ab+bc+ca)-abc]>0
1+(a+b+c)+(ab+bc+ca)+abc>0
(5)
由(3),(4)之結論:
[1-(a+b+c)+(ab+bc+ca)-abc]+[1+(a+b+c)+(ab+bc+ca)+abc]>0
2+2(ab+bc+ca)>0
1+ab+bc+ca>0 |
|